Energy sovereignty and development planning: the case of Maputo, Mozambique. Issue 3 (June 2017) - Broto, Vanesa Castan
Abstract : Energy sovereignty refers to people's capacity to take decisions about energy planning. It emphasises the role of energy services in everyday life. This refers both to the quality of energy services and the inequalities in service provision. Energy sovereignty supports policy agendas to deliver energy access in local settings. It is an alternative to energy security. Energy security casts energy planning at the national level. In contrast, energy sovereignty brings energy questions close to people's homes. This paper focuses on Chamanculo C, a neighbourhood in Maputo (Mozambique). The analysis illustrates three dimensions of energy sovereignty. First, energy sovereignty emphasises a reciprocal relationship between society and ecosystems. Second, energy sovereignty advocates self-determination in relation to business models and technologies. Third, energy sovereignty promotes participation in decision making and innovation. Development planning scholars can deliver an innovative research agenda on energy sovereignty. This should be an action-oriented agenda. It should emphasise opportunities to form partnerships and enhance collaboration. It should put social justice at the centre of energy debates.